1994
DOI: 10.1111/j.1432-1033.1994.tb18734.x
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the O‐specific chain of Legionella pneumophila serogroup 1 lipopolysaccharide

Abstract: The 0-polysaccharide chain of Legionella pneumophila Philadelphia strain 1 (serogroup 1) lipopolysaccharide was investigated by means of 'H-and I3C-NMR spectroscopy, and chemical analysis. It was found to consist of an a-(2+4) interlinked homopolymer of a 5-acetamidino-7-acetamido-8-O-acetyl-3,5,7,9-tetradeoxy-nonulosonic acid possessing most likely the D-glycero-L-galacto configuration, representing the first example of an acidic homopolymer of a higher sugar of this class. The ladder-like banding pattern exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(110 citation statements)
references
References 39 publications
1
102
0
1
Order By: Relevance
“…4A), have been called "Sia-like" molecules (41) and are found in over a dozen bacterial species including L. pneumophila, P. aeruginosa, and pathogenic Vibrio spp (42). Biochemical analysis has shown that Leg and Pse molecules on the surfaces of L. pneumophila, P. aeruginosa, and C. jejuni are modified by O-acetylation (12,14,16). We now show that like the Neu5Ac biosynthetic clusters, both Leg and Pse biosynthetic clusters also include a neuD homolog (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…4A), have been called "Sia-like" molecules (41) and are found in over a dozen bacterial species including L. pneumophila, P. aeruginosa, and pathogenic Vibrio spp (42). Biochemical analysis has shown that Leg and Pse molecules on the surfaces of L. pneumophila, P. aeruginosa, and C. jejuni are modified by O-acetylation (12,14,16). We now show that like the Neu5Ac biosynthetic clusters, both Leg and Pse biosynthetic clusters also include a neuD homolog (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Recently, the structure of the 0-specific chain of LPS of L. pneumophila serogroup 1 strain Philadelphia 1 was elucidated [16]. In order to identify LPS-associated epitopes, a panel of 10 MAbs was employed in the present study.…”
Section: J H Helbig and Othersmentioning
confidence: 99%
“…That allows to do sero-and subtyping of Legionella as demonstrated previously [21]. The O-chain of Legionella LPS consists of a homopolymer of legionaminic acid [26] that exhibits distinct acetylation patterns. These are expected to mediate serologic specificity and antibody binding [28].…”
Section: Discussionmentioning
confidence: 98%